Rock bolting : theory and application in mining and underground construction : proceedings of the International Symposium on Rock Bolting, Abisko, 28 August-2 September 1983 /: theory and application in mining and underground construction : proceedings of the International Symposium on Rock Bolting, Abisko, 28 August-2 September 1983. (2020) - Unknown
No abstract available